Podocyte Injury Augments Intrarenal Angiotensin II Generation and Sodium Retention in a Megalin-Dependent Manner. Issue 3 (September 2019) - Koizumi, Masahiro; Ueda, Kohei; Niimura, Fumio; Nishiyama, Akira; Yanagita, Motoko; Saito, Akihiko; Pastan, Ira; Fujita, Toshiro; Fukagawa, Masafumi; Matsusaka, Taiji
Abstract : We have previously shown that podocyte injury increases the glomerular filtration of liver-derived Agt (angiotensinogen) and the generation of intrarenal Ang II (angiotensin II) and that the filtered Agt is reabsorbed by proximal tubules in a manner dependent on megalin. In the present study, we aimed to study the role of megalin in the generation of renal Ang II and sodium handling during nephrotic syndrome. We generated proximal tubule-specific megalin KO (knockout) mice and crossed these animals with NEP25 mice, in which podocyte-specific injury can be induced by injection of the immunotoxin LMB2. Without podocyte injury, renal Agt staining was markedly diminished and urinary Agt increased in KO mice. However, renal Ang II was similar between KO and control mice on average: 117 (95% CI, 101–134) versus 101 (95% CI, 68–133) fmol/g tissue. We next tested the effect of megalin KO on intrarenal Ang II generation with podocyte injury. Control NEP25 mice showed markedly increased renal Agt staining and renal Ang II levels: 450 (336–565) fmol/g tissue. Megalin KO/NEP25 mice showed markedly diminished Agt reabsorption and attenuated renal Ang II: 199 (156–242) fmol/g tissue ( P <0.001). Compared with control NEP25 mice, megalin KO/NEP25 mice excreted 5-fold more sodium in the urine. Western blot analysis showed that megalin KO decreased NHE3 and the cleaved α and γ forms of Epithelial Na Channel. These data indicate that Agt reabsorbed by proximal tubules via megalin in nephrotic syndrome is converted to Ang II, which may contribute to sodium retention and edema formation by activating NHE3 and Epithelial Na Channel. Abstract : Supplemental Digital Content is available in the text.